Multiple Subchondral Bone Cysts Cause Deterioration of Articular Cartilage in Medial OA of Knee: A 3D Simulation Study - Anwar, Adeel; Hu, Zhenwei; Zhang, Yufang; Gao, Yanming; Tian, Cong; Wang, Xiuying; Nazir, Muhammad Umar; Wang, Yanfeng; Zhao, Zhi; Lv, Decheng; Zhang, Zhen; Zhang, Hu; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Aims To investigate the impact of subchondral bone cysts (SBCs) in stress-induced osseous and articular variations in cystic and non-cystic knee models using finite element analysis. Materials and methods 3D knee joint models were reconstructed from computed tomography (CT) and magnetic resonance imaging (MRI). Duplicate 3D models were also created with a 3D sphere mimicking SBCs in medial tibia. Models were divided into three groups. In group-A, a non-cystic knee model was used. Whereas in groups B and C, SBCs of 4mm and 12mm size were simulated respectively. Cyst groups were further divided into three sub-groups. Each of sub-group 1 was composed of a solitary SBC in anterior half of tibia adjacent to joint-line. In sub-group 2, a solitary cyst was modeled at a lower-joint location and in sub-group 3, two SBCs were used. All models were vertically loaded with weights representing double and single-leg stance. Results During single-leg stance, increase in subchondral bone stress in sub-groups B-1 and B-3 were significant (P=0.044, P=0.026). However in sub-group B-2, a slight increase was observed than non-cystic knee model (9.93±1.94 vs 9.35±1.85; P=0.254). All the sub-groups in group C showed significantly increased articular stress (P<0.001). Conversely, a prominent increase in peri-cystic cancellous bone stress was produced by SBCs in groups B and C (P<0.001). Mean cartilage shear stress in sub-groups B-1 and B-2 (0.66±0.56, 0.58±0.54) was non-significant (P=0.374, P=0.590) as compared to non-cystic model (0.47±0.67). But paired cysts of the same size (B-3), produced a mean stress of 0.98±0.49 in affected cartilage (P= 0.011). Models containing 12mm SBCs experienced a significant increase in cartilage stress (P=0.001, P=0.006, P<0.001) in sub-groups C-1, C-2 and C-3 (1.25±0.69, 1.01±0.54, 1.26±0.59) respectively. Conclusions The presence of large size SBCs produced an increased focal stress-effect in articular cartilage. Multiple cysts further deteriorate the condition by increased osseous stress-effect and high tendency of peripheral cyst expansion in simulated cystic knee models than non-cystic knee models.